Alfalfa snakin-1 prevents fungal colonization and probably coevolved with rhizobia - Garcia, Araceli Nora; Ayub, Nicolás Daniel; Fox, Ana Romina; Gomez, Maria Cristina; Dieguez, Maria Jose; Pagano, Elba Maria; Berini, Carolina Andrea; Muschietti, Jorge Prometeo; Soto, Gabriela Cinthia (BMC Plant Biology, 2018)
Background: The production of antimicrobial peptides is a common defense strategy of living cells against a wide range of pathogens. Plant snakin peptides inhibit bacterial and fungal growth at extremely low concentrations. However, little is known of their molecular and ecological characteristics, including origin, evolutionary equivalence, specific functions and activity against beneficial microbes. The aim of this study was to identify and characterize snakin-1 from alfalfa (MsSN1). Results: Phylogenetic analysis showed complete congruence between snakin-1 and plant trees. The antimicrobial activity of MsSN1 against bacterial and fungal pathogens of alfalfa was demonstrated in vitro and in vivo. Transgenic alfalfa overexpressing MsSN1 showed increased antimicrobial activity against virulent fungal strains. However, MsSN1 did not affect nitrogen-fixing bacterial strains only when these had an alfalfa origin. Conclusions: The results reported here suggest that snakin peptides have important and ancestral roles in land plant innate immunity. Our data indicate a coevolutionary process, in which alfalfa exerts a selection pressure for resistance to MsSN1 on rhizobial bacteria. The increased antimicrobial activity against virulent fungal strains without altering the nitrogen-fixing symbiosis observed in MsSN1-overexpressing alfalfa transgenic plants opens the way to the production of effective legume transgenic cultivars for biotic stress resistance.